DIPLOMASI ENERGI GAS RUSIA DALAM MEMBENDUNG PERLUASAN KEANGGOTAAN UNI EROPA KE UKRAINA (2009) - , Sukarson ([Yogyakarta] : Universitas Gadjah Mada, 2011)
After the collapse of the Soviet Union in 1991, many European countries of the former Eastern Bloc, for reasons of economic betterment, chose to join the European Union. This fact makes Russia feels threatened. Moscow will be weak without the presence of nearby countries who become allies. In 2007, the members of the European Union has reached 27 countries. Russia want to make the European Union membership not grow up, especially from European countries of the former Eastern Bloc. Therefore, when Ukraine had volunteered to join the European Union, Russia tried to prevent it. Russia use gas energy diplomacy for this case. Gas diplomacy was used because both Ukraine and European Union had same dependence on gas supplies from Russia. By stopping the delivery of gas supplies to Ukraine and the European Union, the economic activities and community activities of Ukraine and the European Union could be disrupted, especially in winter. This fact eventually prevent Ukraine to join the European Union and the European Union also canceled their plan to add Ukraine as a member. Russia succeed to prevent the expansion of European Union membership into Ukraine and their gas diplomacy finally increasing Moscow's influence in regional and international level.